Synopsis of the Neotropical Dissomphalus (Hymenoptera, Bethylidae) - Azevedo, C. O. (Zootaxa, 2003)
The following 23 new species are described and illustrated: Dissomphalus alticlypeatus, D. bicerutus, D. cervoides, D. conicus, D. contractus, D. curviventris, D. laticephalus, D. lobicephalus, D. mandibulatus, D. manus, D. thysanus, D. filus, D. truncatus, D. umbilicus, D. spinosus, D. vampirus, D. hemisphaericus, D. ferocus, D. undatus, D. gordus, D. latimerus, D. guttus, D. strabus. Species-groups of conicus, guttus, hemisphaericus, incomptus, laticephalus, gilvipes, punctatus, rufipalpis, strabus and tuberculatus are defined. Diagnoses, descriptions of genitalia, and illustrations of D. archboldi Evans, 1969, D. chiapanus Evans, 1962, D. clypeatus Evans, 1954, D. collaris Evans, 1962, D. confusus, Ashmead, 1894, D. falcatus Evans, 1962, D. nanellus Evans, 1969, D. politus Ashmead, 1894, D. rettenmeyeri Evans, 1964 and D. tuberculatus, Ashmead, 1894 are provided. New data for D. altivolans Evans, 1954, D. apertus Kieffer, 1914, D. basidentatus Azevedo, 1999, D. bilobatus Azevedo, 1999, D. bispinulatus Evans, 1969, D. brasiliensis Kieffer, 1910, D. concavatus Azevedo, 1999, D. curvifoveatus Azevedo, 1999, D. cornutus Evans, 1964, D. digitatusAzevedo, 1999, D. dilatatus Azevedo, 1999, D. extrarramis Azevedo, 1999, D. fungosus Evans, 1979, D. gilvipes Evans, 1979, D. gigantus Azevedo, 1999, D. infissus Evans, 1969, D. krombeini Azevedo, 1999, D. linearis Azevedo, 1999, D. mirabilis Evans, 1966, D. napo Evans, 1979, D. plaumanni Evans, 1964, D. punctatus (Kieffer, 1910), D. rectilineus Azevedo, 1999, D. rufipalpis Kieffer, 1910, D. scamatus Azevedo, 1999, D. stellatus Azevedo, 1999, D. strictus Azevedo, 1999, D. subdeformis Azevedo, 1999, D. triangularis Azevedo, 1999, D. unitus Azevedo, 1999 are given. D. politus and D. tuberculatus have their lectotypes designated. A key to males of Neotropical species is included.